Electoral foundations of parliamentary questions: evidence from the European Parliament. Issue 3 (2nd July 2016) - Sozzi, Fabio
ABSTRACT: Parliamentary questions (PQs) provide a useful tool for members of the European Parliament (MEPs) to control the executive at supranational level and to promote their reputation among relevant groups (party, interest groups and constituency). Previous works have just focused on macro-functions of questions, neglecting the opportunity for MEPs to use them as a re-election and re-selection strategy (micro-functions). In this article, it is argued that PQs are a relevant instrument in the hands of parliamentarians in order to increase their reputation and build up their political image. In particular, it is considered how variation in electoral systems might affect legislative behaviour and, especially, the number of questions asked. Using a new data set on oral and written questions to the European Commission and the Council, the article demonstrates how candidate-centred electoral systems incentivise MEPs to ask more questions than legislators elected under party-centred systems.